ANALYSIS OF INNOVATION TRIGGERS IN THE HANDICRAFT INDUSTRY OF SAUDI ARABIA - Sarah Abdullah Faidhi, Muhammad Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Saudi Arabia is a country with a wide variety of cultures, since each region has its own customs and traditions. Handicraft is one of the preferred industries for Saudi entrepreneurs, as handicrafts represent a significant part of Saudi heritage. They are also important for tourism and for the creation of job opportunities for Saudi citizens. However, modern production and manufacturing methods make it harder for handicraft makers to survive. Thus, this work was done to analyze innovation triggers in the Saudi Arabia handicraft industry. This work was conducted based on qualitative method. For this work, the sample populations were female entrepreneurs in the handicraft industry and the sample size was 8. Data collection was done from interviews with participants. The key findings of this work have shown that most of the entrepreneurs were in business for less than 7 years. The findings of this work have shown that the main trigger for innovation was the sense of originality that were demonstrated by the handicraft products. This has enabled the products to be classified as unique and it has attracted consumers. The ability to apply customization to products is another trigger. The trust they gain from their families and their customers is a very important driver that keeps entrepreneurs motivated.